SOCIOLOGY LITERATURE IN SIMPLE MIRACLES NOVEL BY AYU UTAMI AND ITS PEDAGOGICAL IMPLICATIONS - Teguh Alif Nurhuda; Herman J. Waluyo; Suyitno Suyitno (IJOTL-TL: Indonesian Journal of Language Teaching and Linguistics, 2018)
This study aims to describe the content of the novel Simple Miracles by Ayu Utami in terms of literary sociology studies. In addition, this study also sees its relevance to the learning of literature in high school grade XII. Novel Simple Miracles tells the spiritual story of the main character and his family in everyday life. In addition, in it also told about the relation of society related to religious, social, culture, and residence. This research uses qualitative descriptive method to describe the result of research of literary sociology on Simple Miracles novel. The results of this study indicate a social relationship between the character both in one family member and outside family members. It is that which indicates a relationship or social value in the novel. This novel also has a Javanese cultural value related to its birth and its inner death. The value of sociology literature study on social, religious, and cultural activities can be used as reference material in the study of literature in high school class XII in KD 4.1.